ANALISIS PERAN MOTIVASI INTRINSIK DALAM PROSES PENUNTASAN SKRIPSI MAHASISWA JURUSAN AKUNTANSI FAKULTAS BISNIS DAN EKONOMIKA UNIVERSITAS SURABAYA - Yohana Aprillia Giyanto; Sujoko Efferin (CALYPTRA, 2018)
The research was conducted to analyze the role of intrinsic motivation on the sustainability of accounting students' thesis which is focused and not focused on learning. The basis of this research is due to the lack of research that analyzes the role of intrinsic motivation in accounting learning especially thesis work for students who also while working or married. Using explanatory research with qualitative approach. The study is based on comparing students who focus on learning and students who also have other focus and motivation in doing the learning by conducting interviews, observation, and document analysis. The results showed that intrinsic motivation play a positive rolefor both types of groups of participants either only thesis or who while working or married. The results also indicate that students who while working or married do not negatively affect the learning that is done when having intrinsic motivation in learning. Intrinsic motivation also positively contributes to learning as a person's fuel, forming the roots of the spirit within, enjoying doing something, and making someone accountable.